Prediction of Nitrogen Dosage in 'Alicante Bouschet' Vineyards with Machine Learning Models - Brunetto, Gustavo; Stefanello, Lincon Oliveira; Souza Kulmann, Matheus Severo de; Tassinari, Adriele; Schneider de Souza, Rodrigo Otavio; Rozane, Danilo Eduardo [UNESP]; Tiecher, Tadeu Luis; Ceretta, Carlos Alberto; Avelar Ferreira, Paulo Ademar; Siqueira, Gustavo Nogara de; Parent, Leon Etienne (Mdpi, 2022)
Vineyard soils normally do not provide the amount of nitrogen (N) necessary for red wine production. Traditionally, the N concentration in leaves guides the N fertilization of vineyards to reach high grape yields and chemical composition under the ceteris paribus assumption. Moreover, the carryover effects of nutrients and carbohydrates stored by perennials such as grapevines are neglected. Where a well-documented database is assembled, machine learning (ML) methods can account for key site-specific features and carryover effects, impacting the performance of grapevines. The aim of this study was to predict, using ML tools, N management from local features to reach high berry yield and quality in 'Alicante Bouschet' vineyards. The 5-year (2015-2019) fertilizer trial comprised six N doses (0-20-40-60-80-100 kg N ha(-1)) and three regimes of irrigation. Model features included N dosage, climatic indices, foliar N application, and stem diameter of the preceding season, all of which were indices of the carryover effects. Accuracy of ML models was the highest with a yield cutoff of 14 t ha(-1) and a total anthocyanin content (TAC) of 3900 mg L. Regression models were more accurate for total soluble solids (TSS), total titratable acidity (TTA), pH, TAC, and total phenolic content (TPC) in the marketable grape yield. The tissue N ranges differed between high marketable yield and TAC, indicating a trade-off about 24 g N kg(-1) in the diagnostic leaf. The N dosage predicted varied from 0 to 40 kg N ha(-1) depending on target variable, this was calculated from local features and carryover effects but excluded climatic indices. The dataset can increase in size and diversity with the collaboration of growers, which can help to cross over the numerous combinations of features found in vineyards. This research contributes to the rational use of N fertilizers, but with the guarantee that obtaining high productivity must be with adequate composition.
Keywords: N fertilization; model-building; anthocyanin; total titratable acidity; vineyard management